2018 11th International Symposium on Communication Systems, Networks &Amp; Digital Signal Processing (CSNDSP) 2018
DOI: 10.1109/csndsp.2018.8471861
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Optimized Threshold with SLM based Blanking Non-Linearity for Impulsive Noise Reduction in Power Line Communication Systems

Abstract: High amplitude impulsive noise (IN) occurrence over power line channels severely degrades the performance of Orthogonal Frequency Division Multiplexing (OFDM) systems. One of the simplest methods to reduce IN is to precede the OFDM demodulator with a blanking non-linearity processor. In this respect, Selective Mapping (SLM) applied to an OFDM signal before the transmitter does not only reduce Peak-to-Average Power Ratio (PAPR) but also increases the resulting Signal-to-Noise Ratio (SNR) when blanking nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Nonetheless, there is no evidence on the analysis of the system performance reported in the paper. It should be noted that numerous studies have examined how blanking non-linearity performs over PLC systems, see [16]- [18]. Similar studies were also reported in [19]- [21], to optimise the performances of OFDM receivers.…”
Section: A Prior Workmentioning
confidence: 58%
“…Nonetheless, there is no evidence on the analysis of the system performance reported in the paper. It should be noted that numerous studies have examined how blanking non-linearity performs over PLC systems, see [16]- [18]. Similar studies were also reported in [19]- [21], to optimise the performances of OFDM receivers.…”
Section: A Prior Workmentioning
confidence: 58%
“…It is also noted that high PAPR of the transmitting signal results in more performance degradation by IN. Therefore, a PAPR reduction technique can be applied at transmitter to make the signal robust against an IN affected channel [8]. Another kind of noise, known as Narrowband Interference (NBI), which has small bandwidth and short duration, also degrades a system's performance [9].…”
Section: Introductionmentioning
confidence: 99%